Developing management skills : - Baldwin, Timothy (McGraw-Hill Irwin, 2008)
Developing Management Skills by Baldwin/Bommer/Rubin distinguishes itself by exclusively focusing on teaching relevant skills, its learner-centered writing and its evidence-based foundation. This text’s problem-based approach draws students in with several fundamental and specific questions or challenges in the Manage What?